ACOX1 Gain-of-Function Variant in Two German Pediatric Patients, in One Case Mimicking Autoimmune Inflammatory Disease - Thiels, Charlotte; Lücke, Thomas; Rothoeft, Tobias; Lukas, Carsten; Nguyen, Huu P.; von Kleist-Retzow, Juergen-Christoph; Prokisch, Holger; Grimmel, Mona; Haack, Tobias B.; Hoffjan, Sabine (Neuropediatrics, 2023)
Mitchell syndrome is a very rare genetic disorder due to a specific de novo gain-of-function variant in acyl-CoA oxidase 1 (ACOX1). So far, only five patients with this disease have been described worldwide. We present here two additional unrelated German patients found to carry the same heterozygous ACOX1 N237S variant through exome sequencing (ES). Both patients showed neurodegenerative clinical features starting from ∼4 to 5 years of age including progressive hearing loss, ataxia, ichthyosis, as well as progressive visual impairment leading to amaurosis, and died at the ages of 16 and 8 years, respectively. The first patient was clinically suspected to have anti–myelin oligodendrocyte glycoprotein-antibody-associated myelitis, but the disease course overall deteriorated despite extensive immunomodulatory therapy. The second patient was originally suspected to have a mitochondrial disorder due to intermittent elevated blood lactate. Since Mitchell syndrome has only been identified in 2020, the diagnosis in this second patient was only established through re-evaluation of ES data years after the original analysis. Comparison of all seven reported patients suggests that Mitchell syndrome often (but not always) clinically mimics autoimmune-inflammatory disease. Therefore, in patients with autoimmune central nervous system disease who do not respond adequately to standard therapies, re-evaluation of this diagnosis is needed and genetic analyses such as trio ES should be considered.
Keywords: ACOX1; Mitchell syndrome; exome sequencing